Femoral hydatid cyst: A rare localization of bone echinococcosis: A case report - Nadia El Mahi; Hajar Siouri; Amal Mojahid; Karim Haddar; Hamid Ziani; Siham Nasri; Imane Kamaoui; Imane Skiker (Radiology Case Reports)
Echinococcosis, or hydatid disease, is an endemic disease that affects many regions worldwide and remains a significant public health issue in areas with high endemicity. It is caused by an infection with the dog tapeworm *Echinococcus granulosus*, which is transmitted to humans either through direct contact with dogs or by ingesting contaminated food. This disease primarily affects internal organs, particularly the liver and lungs. Although virtually all organ systems can be involved, bone involvement is possible, especially in the femur. This report presents a case of an extensive hydatid cyst in the femoral bone of a 43-year-old woman, diagnosed late, highlighting the silent nature of bone echinococcosis due to its long latency period. Radiological examinations play a crucial role in the diagnosis, particularly when the disease is detected at an advanced stage. This case emphasizes the importance of early detection through imaging to allow for appropriate management and prevent complications.